An Exploration of The Effect of Teacher’s Positive Reinforcement and Punishment towards Young Learner’s Motivation in 21st Century Learning - I Gede Agus Yuda Mahendra; Ni Luh Putu Sri Adnyani; Ni Putu Era Marsakawati (Jurnal Pendidikan Indonesia, 2024)
The purpose of this study is to explore the effects of teachers' positive reinforcement and punishment on young learners' motivation in 21st-century learning environments. A quantitative research method was employed, utilizing a survey distributed to primary school students across various regions. The data were analyzed using statistical techniques to identify the relationship between the variables. The findings revealed that positive reinforcement significantly enhances student motivation, whereas punishment negatively affects it. The discussion highlights the implications of these results in the context of modern educational practices, where fostering motivation is crucial for young learners' engagement and success. The study concludes that teachers should emphasize positive reinforcement strategies over punishment to create a conducive learning atmosphere. The implications suggest that educational policymakers and practitioners should consider integrating positive behavioral approaches in the curriculum to promote student motivation effectively.